Molecular Characterization of Acute Bee Paralysis Virus (ABPV) and Black Queen Cell Virus (BQCV) in Honeybees (Apis mellifera L. (Hymenoptera: Apidae)) from the Campinas Region - Nogueira, Márcia F.; Malossi, Camila D. [UNESP]; Frediani, Maria Giulia B.; Pereira, David; Prado, Simone de S.; Araujo, João P. [UNESP]; Menezes, Cristiano (Universidade Estadual de Feira de Santana, 2024)
The occurrence of Colony Collapse Disorder (CCD) has prompted extensive research on the role of viruses, including Deformed Wing Virus (DWV), Acute Bee Paralysis Virus (ABPV), and Black Queen Cell Virus (BQCV), in honeybee health. This study investigated the presence and the genetic characteristics of DWV, ABPV, and BQCV in Apis mellifera colonies in a Brazilian apiary in Jaguariúna, SP, Brazil. A total of 11 apparently healthy colonies were sampled, and adult honeybees were submitted to a multiplex PCR. Results showed that six studied colonies tested positive for ABPV in at least one sampling, while one tested positive for BQCV. DWV was not detected, nor were co-infections observed in the sampled colonies. Although the infected colonies did not exhibit clinical signs of disease, the fluctuating presence of ABPV and BQCV suggests temporal variations in viral dynamics, possibly influenced by environmental and nutritional factors. The absence of DWV detection may be attributed to low infestation levels of the Varroa destructor mite in the sampled apiary. Phylogenetic analysis revealed close genetic relationships between the obtained ABPV and BQCV sequences and strains from South America. These findings contribute to the limited knowledge of viral epidemiology in Brazilian honeybee populations.
Keywords: Bee health; bee virus; DWV; molecular detection; Sanger sequencing